2004
DOI: 10.1144/sjg40010023
|View full text |Cite
|
Sign up to set email alerts
|

Composition and provenance of the Silurian to Devonian sandstone sequences of the southern Midland Valley

Abstract: Synopsis A provenance study of rocks from the Silurian inliers and Siluro-Devonian Lanark Group sandstones of the southern Midland Valley has shown that they are petrographically and compositionally similar, and were derived from the same source terrane. The clast content of these rocks indicates that before widespread Lower Devonian calc-alkaline volcanism, this source terrane included volcanic and hypabyssal igneous rocks that appear to have been associated with a wacke sandstone-dominated sediment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 21 publications
0
10
0
Order By: Relevance
“…This Lower Silurian sub-basin architecture continued into the Upper Silurian and controlled the deposition of the redbed fluviatile sandstones and alluvial fan conglomerates which form the lower part of the overlying (and partly Devonian) Lanark Group. Provenance studies, in particular Phillips et al (2004), have shown that strata of the Silurian inliers and Siluro-Devonian Lanark Group sedimentary rocks were derived from the same source, which included volcanic and hypabyssal igneous rocks, a wacke sandstone-dominated sedimentary sequence, granitic plutonic rocks and older metamorphic rocks (also see McGiven 1967;Bluck 1983;Heinz & Loeschke 1988;Syba 1989). Minor differences in sandstone composition between the inliers reflect the influence of the sub-basin architecture on sediment dispersal patterns.…”
Section: The Lower Palaeozoic Strata Of the Midland Valley Terranementioning
confidence: 99%
See 2 more Smart Citations
“…This Lower Silurian sub-basin architecture continued into the Upper Silurian and controlled the deposition of the redbed fluviatile sandstones and alluvial fan conglomerates which form the lower part of the overlying (and partly Devonian) Lanark Group. Provenance studies, in particular Phillips et al (2004), have shown that strata of the Silurian inliers and Siluro-Devonian Lanark Group sedimentary rocks were derived from the same source, which included volcanic and hypabyssal igneous rocks, a wacke sandstone-dominated sedimentary sequence, granitic plutonic rocks and older metamorphic rocks (also see McGiven 1967;Bluck 1983;Heinz & Loeschke 1988;Syba 1989). Minor differences in sandstone composition between the inliers reflect the influence of the sub-basin architecture on sediment dispersal patterns.…”
Section: The Lower Palaeozoic Strata Of the Midland Valley Terranementioning
confidence: 99%
“…Apart from thin calcalkaline, rhyodacitic metabentonite beds (Batchelor & Clarkson 1993) (Phillips et al 1998), none has been recognised unequivocally within the sandstones of the Lanark Basin or older Silurian sub-basins (Phillips et al 2004).…”
Section: The Lower Palaeozoic Strata Of the Midland Valley Terranementioning
confidence: 99%
See 1 more Smart Citation
“…The tectonic evolution of the Midland Valley of Scotland during the Lower Palaeozoic and its setting in Caledonide terrane models have been the focus of much recent debate (Phillips et al 1998(Phillips et al , 2004Smith 1995;McKerrow et al 1991;Williams & Harper 1988). Central to this debate are the palaeontological, sedimentological and structural data from the Silurian rocks of the inliers along the southern margin of the Midland Valley ( Fig.…”
Section: Introductionmentioning
confidence: 99%
“…Waldron et al 2008Waldron et al , 2014 Midland Valley conglomerates. These were derived from the south but from a provenance that is not represented within the currently exposed Southern Uplands Terrane, a circumstance established by a wide range of evidence and discussed by, amongst others, Bluck (1983Bluck ( , 1984, Syba (1989), Stone & Evans (2001) and Phillips et al (2004). The complications and contradictions arising from these provenance mis-matches between terranes as currently positioned have been widely exploredsee Bluck (2013) for a recent comprehensive review -but remain unresolved.…”
Section: Concluding Discussion: Consensus and Outstanding Issuesmentioning
confidence: 99%